1998
DOI: 10.1080/026999498377917
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Objective Performance in Banks

Abstract: Dans cette recherche, on analyse les relations existant entre les leaderships de transaction et de transformation et des indices de performance de vingt banques, cela a partir d'un Cchantillon de quelques 1500 observations. Le comportement de leadership est mesurC griice au Questionnaire Multifactoriel de Leadership (MLQ) qui est applique ici pour la premibre fois a des germanophones. La valeur psychomCtrique du MLQ allemand a CtC analyste et jugCe pas satisfaisante. Nous avons mis au point et contre-valid6 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
92
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 11 publications
9
92
0
2
Order By: Relevance
“…This is in contrast to Howell and Avolio (1993), whose observation was that transformational but not transactional leadership of financial managers positively predicted unit performance over a one year period. Similar observations by Geyer and Steyrer (1998) in an evaluation of managers heading Australian branch banks, reported a stronger positive relationship between transformational leadership and long-versus short term performance.…”
Section: Literature Reviewsupporting
confidence: 60%
See 1 more Smart Citation
“…This is in contrast to Howell and Avolio (1993), whose observation was that transformational but not transactional leadership of financial managers positively predicted unit performance over a one year period. Similar observations by Geyer and Steyrer (1998) in an evaluation of managers heading Australian branch banks, reported a stronger positive relationship between transformational leadership and long-versus short term performance.…”
Section: Literature Reviewsupporting
confidence: 60%
“…For example, Trottier et al (2008) suggested that both transactional and transformational leadership are perceived as important in government settings, although transformational leadership is considered more important. Geyer and Steyrer (1998) reported that transactional leadership predicted the short-term financial performance of bank branches while transformational leadership exhibited stronger predictions over a long period of time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To be specific, this survey includes a set of 36 questions regarding three leadership styles: transformational, transactional, and non-transactional leaderships. This measurement has had wide application in contexts of general leadership, such as delivery firms (Hater and Bass 1988), banks (Geyer and Steyrer 1998), military (Yammarino et al 1993), and general business firms (e.g., health care and service agency) (Tejeda et al 2001), and hotels (Hinkin and Schriesheim 2008). The previous studies indicated acceptable levels of validity and reliability of the measurement.…”
Section: Measurementsmentioning
confidence: 99%
“…Results of past researches show that transformational leadership has been consistently linked to followers' higher level of OCB (Bass, 1985;Organ, 1988;Podsakoff et al, 1990;Howell & Avolio, 1993;Lowe, Kroeck & Sivasubramaniam, 1996;Geyer & Steyrer, 1998;Wang, Law, Hackett, Wang, Chen, 2005;Schlechter & Engelbrecht, 2006;Boerner, Eisenbeiss, Griesser, 2007). On the other hand, the relationship between transactional leadership and OCB has been less empirically examined.…”
Section: Leadership Styles and Ocbmentioning
confidence: 99%